Multiple Reactivations of the Rennick Graben Fault System (Northern Victoria Land, Antarctica): New Evidence From Paleostress Analysis - Cianfarra, P; Locatelli, M; Capponi, G; Crispini, L; Rossi, C; Salvini, F; Federico, L (Tectonics, 2022)
The dense fault network that separates the tectonic units of northern Victoria Land to the E from the East Antarctic Craton to the W represents a regionally sized, NNW-SSE trending deformation zone that is also known as the Rennick Graben Fault system (RGF). This long-lived deformation zone is characterized by great structural complexity, with the superposition and polyphasic reactivation of regional faults; it is known to have been active since the Cambrian-Ordovician, when it formed as a suture zone between different terranes, up to the recent. Its complete framework and geodynamic evolution are still debated and have only been partially investigated. In this research, we explore the Meso-Cenozoic tectonic framework of the RGF by investigating the paleostress fields that characterized the last geodynamic events in the area and their associated brittle deformation. We analyzed faults and fractures data collected at 89 sites during several PNRA ItaliAntartide expeditions and combined fault-slip data inversion with the azimuthal orientation of faults and the spatial distribution of fracture intensities across the RGF. The results from this multi methodological approach confirm the existence of two geotectonic provinces (Bowers Mountains province to the E and Usarp Mountains to the W) characterized by different spatial distributions of brittle deformation, which are significantly more intense in the Bower Mountains domain. Here, the repeated reactivation of the RGF led to the superposition of two recent (Meso-Cenozoic) major tectonic events, with prevalent strike-slip kinematics and characterized by fault reactivation with right-lateral movement overprinting the previous left-lateral event.